Mechanism of Alkaloids and Flavonoids in Bajakah (Uncaria nervosa Elmer) as Antidiabetic Agents - Ridho, Fiki Muhammad (Jurnal Ilmu Medis Indonesia, 2023)
Purpose: Diabetes mellitus is a metabolic disease characterized by hyperglycemic resulting from defects of insulin secretion, insulin action, or both. One of the alternative treatments is bajakah which has antidiabetic activity. This study aims to further discuss the potential and mechanism of alkaloids and flavonoids in bajakah as antidiabetic agents. Method: This study used the literature review method by searching research data on database and 5 articles included for the review. Results: Alkaloids have antidiabetic activity through inhibition of AR, PTP1B, activating AMPK, inhibiting DDP-4 and AGEs, increasing glucose absorption, regenerating pancreatic beta cells, inhibiting and inducing GLUT-4, GSK-3, SREB-1, ACC, PPAR, and glucokinase mechanisms. Meanwhile, flavonoids have activity in pancreatic  beta cell degradation, increasing insulin secretion and sensitivity, glucose homeostasis, glucose absorption through GLUT-2, inhibiting phosphodiesterase, inhibiting alpha glucosidase and  alpha amylase enzymes, inhibiting apoptosis of pancreatic  beta cells, encouraging proliferation, and lowering blood glucose. Limitation: The limitation in this study is that it only used the literature review method which has weaknesses in the data studied. Researcher suggests that more rigorous methods be used in further studies to explore the effectiveness of bajakah in lowering blood glucose level and the need for a toxicity test of bajakah to determine therapeutic doses and lethal doses for the treatment of diabetes mellitus. Contribution: The findings of this study are expected to be a reference in scientific development in the diabetes mellitus treatment using herbal plants. In addition, it is expected that it can increase further knowledge about the mechanism of bajakah as antidiabetic agents.